2005
DOI: 10.1111/j.1471-0528.2004.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifilament polypropylene mesh for urinary incontinence: 10 cases of infections requiring removal of the sling

Abstract: One hundred and forty‐nine women received a suburethral woven polypropylene mesh insertion for urodynamic stress incontinence. Eleven patients (7.5%) presented between 4 and 17 months after surgery (mean 10 months) with symptoms of retropubic infection. Ten patients required surgical exploration, drainage of the collection and removal of the tape either unilaterally (six) or bilaterally (four). Bacterial cultures were negative in nine women. Following removal of the tape, eight patients reported residual incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 7 publications
1
38
0
9
Order By: Relevance
“…Infection is a rare complication of retropubic mid-urethral slings (0.7% of cases) [26]. Bafghi et al [27] report ten cases of intravaginal slingplasty (IVS) prostheses of micropore, multifilamentous polypropylene, totally or partially removed for clinical infection among 149 procedures (6.7% of excision). In this report, bacteriological studies only show one infection due to S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is a rare complication of retropubic mid-urethral slings (0.7% of cases) [26]. Bafghi et al [27] report ten cases of intravaginal slingplasty (IVS) prostheses of micropore, multifilamentous polypropylene, totally or partially removed for clinical infection among 149 procedures (6.7% of excision). In this report, bacteriological studies only show one infection due to S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Bafghi et al [7] reported on 11 out of 149 patients operated with IVS who presented 4-17 months after the operation with symptoms of retropubic infection. Ten patients required surgical removal of the tape in six cases by laparoscopy and in four cases vaginally.…”
Section: Discussionmentioning
confidence: 99%
“…The TVT tape is a macroporous monofilament tape whereas the IVS tape is a multifilament tape with small pores. Previous studies have shown a higher incidence of erosion and extrusion with the IVS tape [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, removal of the entire tape seems to be the best option in cases resistant to conservative treatment, as removal of only the exposed parts of the tape is not sufficient in most patients. Bafghi reported removal of the polypropylene tape in Retzius space abscesses by laparotomy or transvaginally in 60 and 40% of cases, respectively [8]. Baessler et al reported mesh removal vaginally in four, vaginally-laparoscopically in four, and combined vaginal-laparotomy in four patients [9].…”
Section: Discussionmentioning
confidence: 99%